1969
DOI: 10.12669/pjms.301.3968
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Serum Tumor Marker Levels in Gastric Cancer

Abstract: Objective: Tumor markers have shown little benefit as a method for screening. However, they can be used clinically for the monitoring of tumor recurrence and used as prognostic factors because higher levels have been observed in advanced disease. This study aimed to investigate the relationship between the preoperative tumor marker levels and different clinical aspects of gastric cancer. Methods: One hundred and six consecutive patients with confirmed diagnosis of gastric cancer and 106 subjects (age and sex m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Moreover, only elevated CEA was significantly associated with M stage [24]. We also analyzed the association between preoperative serum tumor markers and clinicopathological traits, and found that pT stage, pN stage, M stage and pTNM stage were significantly correlated with the positivity of three tumor markers, which was consistent with previous studies [17, 25].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, only elevated CEA was significantly associated with M stage [24]. We also analyzed the association between preoperative serum tumor markers and clinicopathological traits, and found that pT stage, pN stage, M stage and pTNM stage were significantly correlated with the positivity of three tumor markers, which was consistent with previous studies [17, 25].…”
Section: Discussionsupporting
confidence: 89%
“…Cancer antigen 125 (CA125) is a glycoprotein that is expressed by tissue derived from coelomic epithelium and has a molecular weight estimated to range from 110 to more than 2000 kD [1]. The CA125 serum level has been shown to be increased in women with ovarian cancer and less often in breast [2], lung [3] and gastrointestinal cancers [4]. However, it is not a screening test for malignancies as it may also be elevated in a variety of benign conditions (such as pregnancy, endometriosis, uterine leiomyomata, pelvic inflammatory disease, cirrhosis, peritonitis, pleuritis, pancreatitis, and tuberculosis) [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 82 patients had elevated serum CEA, CA125, or CA199 levels before operation, and 71 cases (86.6 %) had postoperative TM levels reduced or returned to normal. As serum CEA, CA125, and CA199 levels could reflect tumor invasiveness [ 31 ], peritoneal free tumor cells in the ascites [ 32 ], and proliferative activity of tumor cells in ascites or primary tumor [ 33 ], respectively, the reduction of these TM could provide direct evidence that CRS + HIPEC is effective to control PC.…”
Section: Discussionmentioning
confidence: 99%